Analysis of hole quality in drilling GLARE fiber metal laminates. (May 2015) - Pawar, Omanath A.; Gaikhe, Yogesh S.; Tewari, Asim; Sundaram, Ramesh; Joshi, Suhas S.
Abstract: Glass laminate aluminium reinforced epoxy (GLARE) is an advanced aircraft material because of its excellent fatigue crack resistance, high impact strength, high strength-to-weight ratio and high stiffness-to-weight ratio. While drilling on composite/metal stacks has been investigated, the drilling of GLARE, which consists of several alternate thin layers of aluminium and composites, has not been addressed separately in the open literature. The focus of present experimental work is to understand the cutting mechanism and relative effect of cutting parameters and tool geometry on the delamination and burr formation during drilling of GLARE. Thrust force, torque and acoustic emission (AE) signals were acquired for analyzing the cutting mechanism, burr and delamination formation. Also, several measurements of burrs, delamination and hole size were taken in order to understand the hole quality. It has been observed that, 2-fluted drill is the best out of four different geometries used, giving zero delamination and acceptable burr formation followed by the 4-faceted drills. The conventional 3-fluted and 8-faceted drills that are otherwise superior for drilling of fiber reinforced plastics (FRP) composites, performed poorly in drilling of the GLARE laminates. Analyzing the processing parameters, feed again has a dominant role in controlling delamination and burr formation than speed.